Prevalence of drug-resistant tuberculosis in Zimbabwe: A health facility-based cross-sectional survey. (October 2019) - Timire, Collins; Metcalfe, John Z.; Chirenda, Joconiah; Scholten, Jerod N.; Manyame-Murwira, Barbara; Ngwenya, Mkhokheli; Matambo, Ronnie; Charambira, Kelvin; Mutunzi, Herbert; Kalisvaart, Nico; Sandy, Charles
Highlights: The prevalence of RR-TB was [4.0% (95% CI, 2.9, 5.4%) and 14.2% (95% CI, 8.9, 21.1%)] among new and retreatment patients, respectively. The prevalence of MDR-TB was 2.0% (95% CI, 1.3, 3.1%) and 6.4% (95% CI, 2.4, 10.3%) among new and retreatment TB patients, respectively. Weighted prevalence of RR-TB and MDR-TB among new TB patients were 4.6% (95% CI, 3.0, 6.2%) and 1.8% (95% CI, 1.0, 2.5%), respectively. Risk factors for RR-TB included prior TB treatment, self-reported HIV infection, travel outside Zimbabwe for >one month (univariate), and age <15 years. The prevalence of MDR-TB has remained stable since the subnational survey in 1994. Abstract: Objective: To determine the prevalence of resistance to rifampicin alone; rifampicin and isoniazid, and second-line anti-TB drugs among sputum smear-positive tuberculosis patients in Zimbabwe. Design: A health facility-based cross-sectional survey. Results: In total, 1114 (87.6%) new and 158 (12.4%) retreatment TB patients were enrolled. MTB was confirmed by Xpert MTB/RIF among 1184 (93%) smear-positive sputum samples. There were 64 samples with Xpert MTB/RIF-determined rifampicin resistance. However, two were rifampicin susceptible on phenotypic drug susceptibility testing. The prevalence of RR-TB was [4.0% (95% CI, 2.9, 5.4%), n = 42/1043) and 14.2% (95% CI, 8.9, 21.1%; n = 20/141) among new and retreatment patients, respectively. The prevalence of MDR-TB was 2.0% (95% CI, 1.3, 3.1%) and 6.4% (95% CI, 2.4, 10.3%) among new and retreatment TB patients, respectively. Risk factors for RR-TB included prior TB treatment, self-reported HIV infection, travel outside Zimbabwe for ≥one month (univariate), and age <15 years. Having at least a secondary education was protective against RR-TB. Conclusion: The prevalence of MDR-TB in Zimbabwe has remained stable since the 1994 subnational survey. However, the prevalence of rifampicin mono-resistance was double that of MDR-TB.